Optimum programmed intermittent epidural bolus interval time of ropivacaine 0.0625% with dexmedetomidine 0.4 μg/ml at a fixed volume of 10 mL: a randomized controlled trial - Zhong Mei; Qingtao Wang; Shaobo Song; Wenying Lu; Jing Yu (Frontiers Media S.A., 2024)
Background:The aim of our study was to administer adequate local anesthetic in programmed intermittent epidural bolus (PIEB) to avoid breakthrough pain and decrease the use of manual and PCEA boluses. We, therefore, conducted this study to determine the effective PIEB interval time between boluses of ropivacaine 0.0625% with dexmedetomidine 0.4 μg/ml at a fixed volume of 10 mL in 90% of subjects (EI90), without the use of patient-controlled epidural analgesia (PCEA).Methods:A total of 80 subjects were included in the final statistical analysis from 23 August 2022 to 22 November 2022. The subjects were randomly assigned to one of four different PIEB time intervals: 40, 50, 60, and 70 min (groups 40, 50, 60, and 70), respectively. The primary outcome was the effective epidural labor analgesia, defined as no use of PCEA bolus or a manual bolus until the end of the first stage of labor or within 6 hours after loading dose administration. The PIEB EI90 (95% CI) between boluses of ropivacaine 0.0625% with dexmedetomidine 0.4 μg/ml at a fixed volume of 10 mL was estimated using probit regression.Results:The effective PIEB interval time between boluses of ropivacaine 0.0625% with dexmedetomidine 0.4 μg/ml at a fixed volume of 10 mL in 90% of subjects without the use of PCEA was 45.4 (35.5-50.5) minutes using probit regression. No statistical differences were found in the proportion of subjects with Bromage score > 0, hypotension, pruritus, nausea, and vomiting between groups. However, the highest sensory block (pinprick) in the 40-min group was significantly higher than that in the other groups.Conclusion:The estimated value for EI90 for PIEB between boluses of ropivacaine 0.0625% with dexmedetomidine 0.4 μg/ml at a fixed volume of 10 mL using probit regression was 45.4 (35.5-50.5) minutes. Furthermore, future studies are warranted to be established to determine the optimal parameters for different regimens in clinical practice.